Conditioning to Low-Nitrogen Regimes Results in Rice Plants Better Adapted to Low-Nitrogen Stress Through DNA Methylation, Metabolic, and Morpho-physiological Modifications - Pereira, Erinaldo Gomes; Santos, Leandro Azevedo; de Melo, Maria Eduarda Pimentel; Budzinski, Ilara Gabriela Frasson [UNESP]; Amaral, Mayan Blanc; de Souza, Marco André Alves; García, Andrés Calderín; Fernandes, Manlio Silvestre (Springer Nature, 2024)
Nitrogen (N) deficiency is abiotic stress to which rice plants may be frequently exposed. The aim was to investigate whether the exposure of rice plants to complete cultivation cycles with low-N stress results in plants better adapted to this condition. The rice plants, varieties Manteiga and Piaui, were grown for three generations under the following conditions: control, sufficient N (60 kg N ha−1) in all three cycles; NS1, exposed to N stress (10 kg N ha−1) only in the third cycle; NS2 (intermittent stress), exposed to N stress in the first and third cycles; and NS3 (recurrent stress), exposed to N stress in all three cycles. Methylation changes in rice were assessed using methylation-sensitive amplified polymorphism (MSAP). The fully methylated bands increased in all N stress treatments, and the hemi-methylated bands decreased in the most N-stress treatments. This change was more significant in the NS2 and NS3 than in the NS1 treatment, which showed greater N use efficiency, photosynthetic efficiency, and grain yield and quality. NS2 and NS3 treatments promoted distinct changes from NS1 in the expression of genes related to DNA methylation and demethylation, and N metabolism. In addition, alterations in the metabolites content and metabolic pathways were verified. The data obtained in this study show that exposure of rice plants to intermittent and recurrent N stress (i.e., the NS2 and NS3 treatments, respectively) promotes molecular, physiological, and metabolic changes, which together improve N-stress adaptation and result in greater grain yield and quality compared to that in NS1.
Keywords: Methylation; Nitrogen; Photosynthesis; Rice; Stress